Prophet Musa: Analysis of Qs. Al-Kahf Verses 60-82 From The Perspective of Character Education : Nabi Musa: Analisis Qs.Al-Kahfi Ayat 60-82 Ditinjau Dari Perspektif Pendidikan Karakter - Juniawan, Hendro Kartika (Edukasi: Journal of Educational Research, 2023)
This paper discusess the analysis of character education contained in the story of the rihlah ilmiah of the Prophet Musa As., in Qs. Al-Kahf verses 60-82. This research can be categorized as library research, using qualitative methods. Meanwhile in the process of data analysis uses content analysis techniques. This study found that there are at least five character education values contained in the story of the intellectual journey of Prophet Musa As., who is represented as an academic in surah Al-Kahf verses 60-82. The five values of character education that we can learn and emulate today are us follow; First, respect the teacher (Qs. Al-Kahf verse 70). Second, tawadhu or humble (Qs. Al-Kahf verse 60). Third, have high learning ethics and patience (Qs. Al-Kahf verses 60 and 73). Fourth, be critical (Qs. Al-Kahf verses 71, 74, and 77). Fifth, be good attitude or husnudzan towards the teacher (Qs. Al-Kahf verse 82).